Female‐Led High‐Growth: Examining the Role of Human and Financial Resource Management. (2nd December 2018) - Devine, Richard A.; Molina‐Sieiro, Gonzalo; Holmes, R. Michael; Terjesen, Siri A.
Abstract : We integrate research on upper echelons theory, the resource‐based view, and gender to explore conditions that facilitate high growth for female‐led firms. We argue that female entrepreneurs have certain advantages that help them leverage their firms' human and financial capital to achieve high growth. In support, using a sample of U.S.‐based entrepreneurial firms, we found evidence that having a female lead entrepreneur positively moderated the positive relationships between indicators of firms' human and financial capital and high growth. The findings have implications for programs, policies, and practices to encourage more high growth in firms with female lead entrepreneurs.